Valparaíso y las relaciones de Chile con el Reino de Hawai: 1845-1899 - Jara, Mauricio (Revista Notas Históricas y Geográficas, 2021)
Valparaíso y las relaciones de Chile con el Reino de Hawai: 1845-1899